Literature, region, religion: Flannery O’Connor’s essays : Flannery O’Connor’s Essays - Paryż, Marek (Litteraria Copernicana, 2025)
The article discusses the main themes of Flannery O’Connor’s essays collected in her posthumously published book Mystery and Manners (1969). The two eponymous words suggest a kind of dichotomy, but in essence they signify the inseparability of the social and the religious in O’Connor’s writing. According to the writer, manners shape attitudes which in turn decide about the quality of collective life. The realm of manners, governed by logic, does not determine human life in its entirety because it possesses a hardly definable additional dimension, encapsulated in the term “mystery.” O’Connor ascribes a religious meaning to it, but in her fiction it manifests itself through happenings that confront her characters with phenomena that transcend their familiar experiential territory. The notions of manners and mystery correspond with the literary categories of regional writing and Catholic writing, which O’Connor problematizes in her essays.